Development of Applicative-Integrative Student Worksheet Based on Scientific Approach on Reaction Rate Subject - Siti Mutmainah; Usman Usman; Mukhamad Nurhadi (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2018)
This research aimed to design applicative-integrative student worksheet based on scientific approach, which was applied to the learning process by using guided inquiry learning model. The worksheet was properly assessed from three aspects. There were validity, effectivity and practicality. The approach used in this research was ADDIE approach (Analysis, Design, Development, Implementation and Evaluation) with Embedded Mixed Methods. The stages of this research were extraction of potentials and problems, designing student worksheet, validation by experts including media, subjects, and practitioners, then testing the student worksheet. The results showed that the student worksheet was appropriate based on the analysis of the data obtained. This student worksheet was feasible to be implemented in the learning process of chemistry class, particularly reaction rate subject. The result of this research showed that validity, effectivity and practicality obtained 93.9, 83.1, and 94.3%, respectively.